The Influence of Price Earning Ratio and Price to Book Value on Stock Return in Food and Beverage Companies Listed on Indonesia Stock Ex-change in 2016-2020 - Yetti Tri Wulandari (Jurnal Akuntansi dan Perpajakan, 2022)
This study aims to examine the effect of PER and PBV on stock returns. The variables used are Price Earnings Ratio (PER) and Price to Book Value (PBV). The population in this study are Food and Beverage Companies listed on the Indonesia Stock Exchange in 2016-2020. And there are 30 samples studied in this study. The data analysis method used is multiple linear regression analysis. The results of this study indicate that the PER ratio has a significant negative effect on Stock Return it means the higher the ratio will indicate that the company’s performance is getting better; on the contrary, if the Price Earnings Ratio is too high, it can also indicate that the stock price offered is already high or irrational. Meanwhile, PBV has a significant positive effect on Stock Return because when PBV increases, stock returns also increase, it means the higher the PBV ratio will make investors more confident in the company so that the more investors who carry out investment activities, the higher the stock return will be.